Development of a self-report scale to assess relaxation effects of flavors and fragrances - Yoko Hosokawa; Yukio Goto; Kunihide Hoshino; Kensuke Okada (Scientific Reports)
Abstract Stress is a modern social problem, and it is critical to cope with stress effectively to maintain one’s mental health. Several studies have demonstrated that relaxation helps alleviate depression and anxiety. Although several studies have assessed the relaxation effects of odors, currently, no unified method exists that measures these subjective effects properly and efficiently. To address this gap, we developed the Relaxation Scale of Flavors and Fragrances (RSFF) and examined its structure, reliability, and validity. Two repeated surveys were administered among 110 participants to assess the relaxation effects of flavors and fragrances. The exploratory factor analysis results based on the first survey revealed a three-factor structure as follows: liberation, nostalgia, and negative emotions. Confirmatory factor analysis based on the second survey confirmed this structure. Reliability testing confirmed excellent internal consistency based on Cochran’s alpha, and satisfactory test–retest reliability based on the correlation coefficient between the two repeated surveys’ results. Correlations with the Profile of Mood States revealed satisfactory construct validity. This study’s findings establish the RSFF as a tool for assessing the subjective relaxation effects of flavors and fragrances.